Manifesting Ecofeminism in Peatland Restoration: Policies, Actions, and Challenges - Safitri, Myrna Asnawati (Jurnal Perempuan, 2020)
Degradation of peatland ecosystems occurs as a result of excessive exploitation leading to peat drainage and fires. This was influenced by a masculinity perspective in resource tenure and utilization. Ecofeminism presents a different perspective on narratives and inter-relationships of human with nature, including the place of women in them. Injustice that befalls women occur due to unequal power relations in the control and utilization of resources in the peatland ecosystem. This paper discusses the Government of Indonesiaâ€™s efforts to reduce gender injustice through Peatland Restorationâ€™s policy. Two policies are discussed here, namely the Social Safety Safeguard and Peat Cares Village Program. It is concluded that women's participation must be able to resolve the imbalance of power relations among women as well as between gender. This requires sufficient time and everlasting education.Â